The Influence Of Financial Literacy And Lifestyle On Decisions To Take Credit At PT. BPR Hasamitra Makassar - Claudio Julio Mongan; Amika Sapan; Normiani Monda (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This research was conducted with the aim of knowing whether the effect of financial literacy and lifestyle on credit-taking decisions and whether financial literacy and lifestyle simultaneously influence PT. BPR Hasamitra Makassar by using a quantitative research model. The sample used in this study was 50 respondents using the data analysis method. The r-square test is the coefficient of determination in endogenous constructs, F-square in statistics is a statistical testing method used to compare several population averages simultaneously (simultaneous, Path coefficient The Path Coefficient is used to show how strong the effect or influence of the independent variable is on the dependent variable and the T test One of the statistical tests used to test the truth or falsity of the hypothesis which states that between two mean samples taken randomly from the same population, there is no difference which is significant. From the results of the research conducted on the effect of financial literacy and lifestyle on credit decision making at PT. BPR Hasamitra Makassar, the results obtained from the analysis carried out are the results of the hypothesis test showing that financial literacy and lifestyle have an influence on the decision to take credit. Financial Literacy has an influence on debtor's borrowing decisions, Lifestyle has an influence on debtor's borrowing decisions. Financial literacy and lifestyle have a simultaneous influence on the decision to take credit. Keywords: Literacy, finance, lifestyle, decisions, taking credit.